2010
DOI: 10.1108/17260531011086144
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type and volume fraction (VF) of steel fiber on the mechanical properties of self‐compacting concrete

Abstract: PurposeSelf‐compacting concrete (SCC) offers several economic and technical benefits; the use of steel fibers extends its possibilities. Steel fibers bridge cracks, retard their propagation, and improve several characteristics and properties of the SCC. The purpose of this paper is to investigate the effects of type and volume fraction of steel fiber on the compressive strength, split tensile strength, flexural strength and modulus of elasticity of steel fiber reinforced self‐compacting concrete (SFRSCC).Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The correlation of the compressive strength and the modulus of elasticity is also seen to have an incremental trend. This is because of increased compressive strength, which results in stronger and denser cement paste matrix and interface and also better matching of the elastic properties of cement paste matrix and aggregate resulting in higher modulus of elasticity of concrete (Gutierrez and Canovas, 1995; Ghanbarpour et al , 2010; Khaleel et al , 2011; Craeye et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation of the compressive strength and the modulus of elasticity is also seen to have an incremental trend. This is because of increased compressive strength, which results in stronger and denser cement paste matrix and interface and also better matching of the elastic properties of cement paste matrix and aggregate resulting in higher modulus of elasticity of concrete (Gutierrez and Canovas, 1995; Ghanbarpour et al , 2010; Khaleel et al , 2011; Craeye et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the experimental trends obtained in this study. Highest STS was observed in C-93 after 28 and 90 days of curing which was 8% and 10% in comparison to the reference mix, respectively (Ghanbarpour et al , 2010). As seen in Figure 5, STS of C-84, C-87, C-88, C-92 and C-93 were higher to reference mix.…”
Section: Resultsmentioning
confidence: 99%
“…When h f reaches the critical depth, ε tc and ε tu simultaneously reach the cracking strain, respectively. In the critical state, taking ε tc and ε tu as known quantities into equation (2), the critical depth of the MSFRC layer h fcr can be obtained. If h f < h fcr , the strain of the normal concrete at cracking ε tc is known, while ε tu is variable; then the relationship between the depth of the MSFRC layer h f and the cracking moment of the beam M cr can be obtained by taking the cracking strain ε tc into (2).…”
Section: Critical Depth Of Msfrc Layer Of the Partially Reinforced Beam Based On Strength Theorymentioning
confidence: 99%
“…Compared with conventional concrete, steel fibers reinforced concrete (SFRC) has excellent mechanical properties and durability [1]. However, in a large number of related studies on SFRC, the typical steel fiber employed in concrete matrix is generally 0.5 to 0.8 mm in diameter or equivalent diameter, 30 to 60 mm in length, and 0.5% to 3.0% in the fiber volume fraction [2][3][4]. In recent years, microsteel fibers have been used in high performance concrete [5][6][7][8][9], usually with the diameter about 0.2 mm, which have shown that [10][11][12] the crack-retarding and toughening effect of the Type I microsteel fiber (usually smooth cold-drawn wire with about 0.2 mm in diameter) in SFRC are better than those of the larger diameter steel fiber, while the effect of the Type II micro steel fiber (deformed cut sheet) remains to be studied.…”
Section: Introductionmentioning
confidence: 99%